2012
DOI: 10.1002/phar.1040
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Atorvastatin‐Associated Hearing Loss

Abstract: Drug-associated ototoxicity is a potentially irreversible adverse event. Among the several 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (statins) available in the United States, only atorvastatin is associated with tinnitus, but none are associated with any forms of hearing loss. A search of the published literature (1950-August 2011) revealed no published case reports of ototoxicity associated with statins. To our knowledge, we describe the first case of progressive, irreversible hearing loss in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…Common adverse drug events (ADEs) or adverse drug reactions (ADRs) for patients taking ATO include arthralgia, dyspepsia, diarrhea, nausea, nasopharyngitis, insomnia, urinary tract infection and pain in the extremities 13. Additionally, ATO-associated myalgia,11 hearing loss,14 and hepatotoxicity15,16 are often reported. Idiosyncratic liver injury associated with statins is rare but can be associated with severe outcomes,17 and the research on this topic is incomplete but extremely necessary 18…”
Section: Introductionmentioning
confidence: 99%
“…Common adverse drug events (ADEs) or adverse drug reactions (ADRs) for patients taking ATO include arthralgia, dyspepsia, diarrhea, nausea, nasopharyngitis, insomnia, urinary tract infection and pain in the extremities 13. Additionally, ATO-associated myalgia,11 hearing loss,14 and hepatotoxicity15,16 are often reported. Idiosyncratic liver injury associated with statins is rare but can be associated with severe outcomes,17 and the research on this topic is incomplete but extremely necessary 18…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of hearing loss was mentioned as common or uncommon, according to the SmPC. It is rare but well described for phosphodiesterase inhibitors , quinine and hydroxychloroquine , atorvastatin , macrolides , and antifungal drugs such as amphotericin B . Cases of hearing loss were observed with fluoroquinolones, imipenem, and isotretinoin according to their SmPC.…”
Section: Discussionmentioning
confidence: 99%
“…They detected a statistically significant relationship between SSNHL and previous statin use, regardless of whether statin is used regularly. Liu M. et al [22] reported a progressive and irreversible hearing loss in a 32-year-old male patient after atorvastatin treatment at 18 months. The patient described recurrent and spontaneously recovering hearing loss six months after the start of treatment.…”
Section: Discussionmentioning
confidence: 99%